(untitled) (Archaeologia Adriatica, 2011)
Excavations of three tumuli at Ljubačka Kosa were conducted in 2007 as part of field studies for archaeology students at the Department of Archaeology of the University of Zadar. On this occasion, seven inhumations and numerous grave goods were unearthed, among which tumulus 1 particularly stands out. the unearthed items enabled the dating of the tumuli to approximately the second stage of the Liburnian culture or 8th-7th century Bc.